Working conditions and mental illness among nursing workers - Pereira, Mirian Caroline; Eberhardt, Leonardo Dresch; de Carvalho, Manoela [UNESP] (EDITORA SCIENTIFIC, 2024)
The growth of mental illness has aroused the interest of the occupational health area in the study of the relationship between work and mental health. Among health workers, nursing represents the largest contingent of workforce in the sector and, due to frequent exposure to numerous stressors, they present a significant increase in work-related mental illness. The objective of this study was to identify the most frequent illness and mental distress processes among nursing professionals in Brazil and relate them to working conditions and coping strategies described in recent scientific literature. The integrative review was conducted in electronic health databases, in May 2020, and resulted in the selection and analysis of 17 studies. The results show that the hospital environment and its working conditions, overload of activities, precarious working conditions, short deadlines to carry out activities and conflicting relationship with the team and users constitute the main scenario of studies on illness and mental distress of nursing workers. The most frequent illness and mental distress processes involve the consequences of stress such as: anxiety, demotivation, bad mood, body aches, musculoskeletal disorders, irritability, alteration of menstrual flow, insomnia, attention and concentration deficit, gastric and duodenal ulcers, fatigue, migraines, among others. The strategies adopted by workers to minimize work stress are predominantly individual, pointing to a gap in studies, or in reality itself, about collective strategies.
Condições de trabalho e adoecimento mental entre profissionais de enfermagem
Keywords: mental health; nursing staff; occupational health